(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
Taxes regulate life. No matter the historical period, your payment will influence the life of the society. Depending on changes in a tax system, a state can raise it’s economy and provide public services to the entire population. On the other hand, there are also changes that may leave this same country on the verge of collapse, given the uncontrolled increase in public debt or, even worse, on the social inequality. In this way, tributes existing or inserted in a state can save it or leave it in a economic crisis, and, consequently, a social crisis. One of these tributes, the Individual Income Tax, deserves an extreme focus. The purpose of this tax is to balance the income acquired so that whole population has a fair quality life. That is, Individual Income Tax must redistribute part of the income to the poorest sector, but without discouraging the investments of the richest. Yet, this balance between distributing and don’t desistimulate generated a problem that introduced to several positions. For this reason, the theoretical references sought to be as bilateral as possible. It should be emphasized that a system of effective income taxation will not only increase the life quality in Brazil, but will also be one of the bases of its economic recovery. Both unemployment and failing investment can decline with the right income taxation. So, this article seeks to compare historical data and models used by countries such as the United States, New Zealand and Estonia.